ANALISIS DAYA SAING DAN FAKTOR DETERMINAN YANG MEMPENGARUHI EKSPOR UDANG INDONESIA - Br Siboro, Sonia Falentina Harta; Putu Widanta, Anak Agung Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Shrimp is the leading non-oil and gas export commodity as well as the Indonesian fishery sub-sector. Shrimp commodity is also a commodity that has high competitiveness because it has fluctuating exports in the period 2013-2020. The purpose of this study was to determine how the condition of competitiveness of Indonesian shrimp commodities and the influence of competitiveness, production, GDP per capita and foreign exchange rates ( US$) partially and simultaneously on Indonesian shrimp exports in five export destination countries (United States, Japan, China, Malaysia, Canada). The data used in this study is panel data. Panel data is a combination of time series and cross section. To analyze the competitiveness of Indonesian shrimp commodities in five destination countries, the RCA (Revealed Comparative Advantage) method was used. The RCA values ??for the five destination countries show that Indonesian shrimp exports have strong competitiveness. Based on the research results, competitiveness, production, GDP per capita and foreign exchange rates simultaneously have a significant influence on Indonesia's shrimp exports. Partially competitiveness, GDP and foreign exchange rates have a positive and significant impact on Indonesia's shrimp exports. Meanwhile, production has a negative and insignificant effect on Indonesian shrimp exports